(3GdUaGJs - (3LGHQ Hf MjGf Hf YHO Gddg Gdchaj, CHh ehSi, J (B200 (3g` s ((3HdOI JHQjR s)
(3ChdgG (B:s
(3Ef Gddg JYGdi GeJf Ydi GdfGS HgPg GdcJH efg YXjeI aef bQC cJHfG ade jNQL dg eGfbhdg Ef cGf eQehRkG s
(3BNQgG (B:s
(3hYdi bOQ eG jbGheg ef GdHGQO GdQWH ai GdeYOI GdPi gh VOg Hd Jchf SQYI GdgVe hEHWGFg aGYQa Pdc Ef TGA Gddg JYGdi s
(3Vef eLehY , JQJjHgG (B: (3ef U (B68 - (3U(B77s
(3GdfSNI HgG MhGTs
(3hQO PcQg ai Qbe (B96 (3hgh GdebGdI GdSGOSI ef cJGH GdSHYjfs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B103 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B105s
Keywords: (3GdcjejGA h GdWHjYjGJs